Linking parental self-efficacy, parenting behaviour and mental health of Malaysian early adolescents - Dzeidee Schaff, Anis Raihan; Zulkefly, Nor Sheereen; Ismail, Siti Irma Fadhilah; Mohd Nazan, Ahmad Iqmer Nashriq (Springer, 2024)
The impact of parental characteristics on mental health outcomes of early adolescents have been robustly examined in the West. However, the extent to which two salient parental characteristics, specifically parental self-efficacy (PSE) and parenting behaviours (PB) influence early adolescents’ mental health particularly emotional-behavioural problems and competence are scarcely explored among Asian households. Hence, this study examined the linkages between PSE, PB (i.e., warmth, monitoring, harsh discipline, and indigenous), and early adolescents’ mental health (i.e., emotional-behavioural problems and competence) from the perspective of Malaysian parents. The mediating role of PB on the relationships between PSE and early adolescents’ mental health was also examined. Sample comprised 478 Malaysian parents of children aged between 10 and 14 years old. Parents completed a self-report online survey regarding their PSE and PB as well as child’s mental health. Structural equation modelling (SEM) analysis indicated that PSE was positively related to parental warmth, monitoring, and indigenous parenting which predicted better early adolescents’ mental health, but negatively related to parental harsh discipline that predicted poorer early adolescents’ mental health. Results also show that high PSE is related to less emotional-behavioural problems and more competence among early adolescents. Finally, the role of warmth, monitoring, and harsh discipline parenting was established as the mediators between the relationships between PSE and early adolescents’ mental health. The findings imply that parents’ belief in their ability to perform their parenting roles and the way they behave in their parenting could have a direct and indirect impact on their offspring’s mental health. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.